Widespread activation of microglial cells in the hippocampus of chronic epileptic rats correlates only partially with neurodegeneration - Papageorgiou, Ismini E.; Fetani, Andriani F.; Lewen, Andrea; Heinemann, Uwe; Kann, Oliver (Brain structure & function, 2015)
Activation of microglial cells (brain macrophages) soon after status epilepticus has been suggested to be critical for the pathogenesis of mesial temporal lobe epilepsy (MTLE). However, microglial activation in the chronic phase of experimental MTLE has been scarcely addressed. In this study, we questioned whether microglial activation persists in the hippocampus of pilocarpine-treated, epileptic Wistar rats and to which extent it is associated with segmental neurodegeneration. Microglial cells were immunostained for the universal microglial marker, ionized calcium-binding adapter molecule-1 and the activation marker, CD11b (also known as OX42, Mac-1). Using quantitative morphology, i.e., stereology and Neurolucida-based reconstructions, we investigated morphological correlates of microglial activation such as cell number, ramification, somatic size and shape. We find that microglial cells in epileptic rats feature widespread, activation-related morphological changes such as increase in cell number density, massive up-regulation of CD11b and de-ramification. The parameters show heterogeneity in different hippocampal subregions. For instance, de-ramification is most prominent in the outer molecular layer of the dentate gyrus, whereas CD11b expression dominates in hilus. Interestingly, microglial activation only partially correlates with segmental neurodegeneration. Major neuronal death in the hilus, CA3 and CA1 coincides with strong up-regulation of CD11b. However, microglial activation is also observed in subregions that do not feature neurodegeneration, such as the molecular and granular layer of the dentate gyrus. This in vivo study provides solid experimental evidence that microglial cells feature widespread heterogeneous activation that only partially correlates with hippocampal segmental neuronal loss in experimental MTLE.
Published online: 31 May 2014
Gesehen am 30.06.2020